Searching for Success—Entrepreneurs' Responses to Crowdfunding Failure. (May 2021) - Piening, Erk P.; Thies, Ferdinand; Wessel, Michael; Benlian, Alexander
In this study, we seek to provide new insights into the process of problemistic search by examining entrepreneurs' behavioral responses to failures. Using a comprehensive dataset of over 65, 000 crowdfunding projects, we specifically explore how negative performance feedback influences entrepreneurs' search distance. Our results demonstrate that the severity and persistence of failure have a U-shaped and inverted U-shaped relationship with search distance, respectively. Moreover, greater temporal distance between an entrepreneur's failure experience and a subsequent crowdfunding project is not only associated with increases in search distance, but also attenuates the curvilinear main effects.